Elevated temperature and ozone modify structural characteristics of silver birch (Betula pendula) leaves. (20th December 2019) - Hartikainen, Kaisa; Kivimäenpää, Minna; Nerg, Anne-Marja; Mäenpää, Maarit; Oksanen, Elina; Rousi, Matti; Holopainen, Toini
Abstract: To study the effects of slightly elevated temperature and ozone (O3 ) on leaf structural characteristics of silver birch ( Betula pendula Roth), saplings of four clonal genotypes of this species were exposed to elevated temperature (ambient air temperature +0.8–1.0 °C) and elevated O3 (1.3–1.4× ambient O3 ), alone and in combination, in an open-air exposure field over two growing seasons (2007 and 2008). So far, the impacts of moderate elevation of temperature or the combination of elevated temperature and O3 on leaf structure of silver birch have not been intensively studied, thus showing the urgent need for this type of studies. Elevated temperature significantly increased leaf size, reduced non-glandular trichome density, decreased epidermis thickness and increased plastoglobuli size in birch leaves during one or both growing seasons. During the second growing season, O3 elevation reduced leaf size, increased palisade layer thickness and decreased the number of plastoglobuli in spongy cells. Certain leaf structural changes observed under a single treatment of elevated temperature or O3, such as increase in the amount of chloroplasts or vacuole, were no longer detected at the combined treatment. Leaf structural responses to O3 and rising temperature may also depend on timing of the exposure during the plant and leaf development as indicated by the distinct changes in leaf structure along the experiment. Genotype-dependent cellular responses to the treatments were detected particularly in the palisade cells. Overall, this study showed that even a slight but realistic elevation in ambient temperature can notably modify leaf structure of silver birch saplings. Leaf structure, in turn, influences leaf function, thus potentially affecting acclimation capacity under changing climate.